Association of Complementary and Alternative Therapies With Mental Health Outcomes in Pregnant Women Living in a Postdisaster Recovery Environment. (September 2016) - Barcelona de Mendoza, Veronica; Harville, Emily; Savage, Jane; Giarratano, Gloria
Purpose: The objective of this study was to determine if complementary and alternative medicine therapies are associated with mental health in postdisaster environments.Design: Pregnant women ( N = 402) were interviewed between 2010 and 2012 as part of a larger cross-sectional study on hurricane recovery and models of prenatal care.Methods: Symptoms of depression (Edinburgh Postnatal Depression Screen), prenatal anxiety (Revised Prenatal Distress Questionnaire), posttraumatic stress (PCL-S), and perceived stress (PSS) were examined. Logistic regression was used to adjust for income, race, education, parity, and age. The most commonly reported therapies were prayer, music, multivitamins, massage, and aromatherapy.Findings: Mental illness symptoms were common (30.7% had likely depression, 17.4% had anxiety, and 9.0% had posttraumatic stress). Massage was protective for depression (Edinburgh Postnatal Depression Index [EDSI] >8; adjusted odds ratio [aOR] = 0.6, 95% confidence interval [CI] = 0.3-0.9), while use of aromatherapy (aOR = 1.9, 95% CI = 1.1-3.2) and keeping a journal (aOR = 1.9, 95% CI = 1.1-3.2) were associated with increased odds of depression. Aromatherapy was associated with symptoms of pregnancy-related anxiety (aOR = 2.0, 95% CI = 1.1-3.8).Conclusions: Symptoms of mental illness persist after disaster, when untreated. Nurses should consider assessing for complementary and alternative medicine utilization in pregnancy as a potentially protective factor for mental health symptoms.